Measurement of the muon neutrino charged-current single π+ production on hydrocarbon using the T2K off-axis near detector ND280 - Abe, K; Akutsu, R; Ali, A; Alt, C; Amey, J; Andreopoulos, C; Anthony, L; Antonova, M; Aoki, S; Ariga, A; Ashida, Y; Atkin, ET; et al. (American Physical Society, 2020)
We report the measurements of single and double differential cross section of muon neutrino charged-current interactions on carbon with a single positively charged pion in the final state at the T2K off-axis near detector using $5.56×10^{20}$ protons on target. The analysis uses data control samples for the background subtraction and the cross section signal, defined as a single negatively charged muon and a single positively charged pion exiting from the target nucleus, is extracted using an unfolding method. The model dependent cross section, integrated over the T2K off-axis neutrino beam spectrum peaking at $0.6$~GeV, is measured to be $σ = (11.76 ± 0.44 \text{(stat)} ± 2.39 \text{(syst)}) × 10^{-40} \text{cm}^2$~$\text{nucleon}^{-1}$. Various differential cross sections are measured, including the first measurement of the Adler angles for single charged pion production in neutrino interactions with heavy nuclei target.